Concept Raps versus Concept Maps: A Culturally Responsive Approach to STEM Vocabulary Development - Jamaal Young; Jemimah Young; Marti Cason; Nickolaus Ortiz; Marquita Foster; Christina Hamilton (MDPI AG, 2018)
This article argues that the development of rap song lyrics or lyrical concept mapping can be a viable pedagogical alternative to the development of concept maps as a means to reinforce STEM vocabulary. Hip-hop pedagogy is a culturally responsive pedagogy that leverages the funds of knowledge acquired from hip-hop culture. Unfortunately, many students with strong hip-hop cultural identities may lack equally strong mathematics identities. Given the success of hip-hop pedagogies within the science content area, we posit that hip-hop pedagogies are appropriate in other STEM content areas such as mathematics. Concept mapping is an instructional tool that has been empirically validated as an effective means to develop strong conceptualizations of mathematics content. While hip-hop pedagogy is well established in the science content area, it remains underdeveloped within mathematics education. We argue that the lyrical structure of a rap song is fundamentally similar to the structure of a concept map. This article provides a framework to support lyrical concept mapping as a culturally responsive instructional tool that can be used as an alternative to traditional concept mapping. Special attention is placed on the use of hip-hop pedagogy to affirm and empower dually marginalized students.